Ladder Of Participation: Capacity Development For The Elderly Through Prolanis - Setijaningrum, Erna (Opción, 2019)
This study aims to know learn of the participation of the elderly in the capac- ity development process, and then to see what factors influence the success of capacity development. The research location was in the community health centres namely Medokan Ayu of Surabaya, the Sumbersari of Jember, and the Pandian of Sumenep. The results of this study indicate the conclusion that there are different factors that influence the success of elderly capacity devel- opment through Prolanis in a big city, medium city and small city. The success in the big city and middle city is more influenced by the active participation of the elderly. The success in the small city is more influenced by the strong commitment of the apparatus of community health centre.